Proper Collaboration between Social Impact and ESG in Long-term Care - Martin, Zsarnoczky (Magyar Gerontológia, 2023)
New terminologies induce new solutions that affect long-term care actors. ESG (Environmental, Social, and Governance) provides globally new standards that stakeholders use to measure their impact on society and the environment. In this changing environment, long-term care facilities are no exception as well in this process. Social impact is one of the three pillars of ESG and refers to the positive or negative effects that a company's activity has on society affects the term of the social responsibility.